The role of supply chain integration in strengthening the performance of not-for-profit organizations: evidence from the food banking industry. Issue 2 (31st March 2020) - Ataseven, Cigdem; Nair, Anand; Ferguson, Mark
Abstract : Purpose: This paper investigates the inter-relationships among supply integration, demand integration and internal integration in the context of food banking. Design/methodology/approach: This study utilizes survey data from managers at 71 different food banks in the US combined with secondary data gathered from Feeding America's website to provide model controls and an objective measure of food bank performance. The performance metric is the amount of food distributed per food insecure individual in the food bank's service area. Theoretically developed hypotheses were tested using seemingly unrelated regression techniques and a Monte Carlo simulation-based mediation analysis. Findings: While the previous research on integration relationships on for-profit supply chains has shown that managing internal integration forms the foundation for integrating with suppliers and customers, the findings indicate that, for not-for-profit food banks, external integration should precede internal integration and that demand integration has a stronger influence on performance than supply integration. Research limitations/implications: The heavy reliance of food banks on external partners necessitates an internal integration structure that supplements and builds upon these external relationships. The basic programs thus developed have a direct impact on the amount of food distributed per food insecure individual. Originality/value: This paper contributes to the humanitarian supply chain management literature by analyzing supply chain integration and its performance implications in a slow onset disaster setting.